Domain bifurcation as a customisation and business intelligence strategy in domain-driven innovation - Meersman, Davor (IADIS, 2012)
Bifurcation of domain models is introduced as a strategy for customisation and business intelligence in a Malaysian real estate CRM system. The process of bifurcation forms part of a broader strategy in the context of domain-driven innovation. The overarching approach is described, the bifurcation process and resulting domain models are discussed, and the results of the approach are analysed.